Engineering Bipolar Doping in a Janus Dual-Atom Catalyst for Photo-Enhanced Rechargeable Zn-Air Battery - Liu, Ning; Li, Yinwu; Liu, Wencai; Liang, Zhanhao; Liao, Bin; Yang, Fang; Zhao, Ming; Yan, Bo; Gui, Xuchun; Yang, Hong Bin; Yu, Dingshan; Zeng, Zhiping; et al. (Nano-Micro Letters, 2025)
Harnessing solar energy to enhance the rechargeable zinc–air batteries (RZABs) performance is a promising avenue toward sustainable energy storage and conversion. Simultaneously enhancing light-absorption capacity and carrier separation efficiency in nanomaterials, as well as improving electrical conductivity and configuration for electrocatalysis, presents a formidable challenge due to inherent trade-offs and interdependencies. Here, we have developed a Janus dual-atom catalyst (JDAC) with bifunctional centers for efficient charge separation and electrocatalytic performance through a bipolar doping strategy. The in situ X-ray absorption near-edge structure and Raman spectroscopy analyses demonstrated that the Ni and Fe centers in JDAC not only function as effective sites for oxygen evolution reaction and oxygen reduction reaction, respectively, but also serve as efficient hole and electron enrichment sites, effectively suppressing photoelectron recombination while enhancing photocurrent generation. As a result, the assembled JDAC-based light-assisted RZABs exhibited extraordinary stability at large current densities. This work delivers pivotal insight to design Janus dual-atom catalysts that efficiently convert solar energy into electric and chemical energy. Highlights: 1 Janus dual-atom catalyst (JDAC) with bifunctional centers was synthesized via a single-step bipolar doping strategy to promote efficient charge separation and superior electrocatalytic performance. 2 The in situ X-ray absorption near-edge structure and Raman spectroscopy analyses demonstrated that Ni and Fe centers in JDAC function as effective sites for oxygen evolution reaction and oxygen reduction reaction, and effectively suppress photoelectron recombination while enhancing photocurrent generation. 3 The assembled JDAC-based light-assisted rechargeable zinc–air batteries exhibited extraordinary stability at large current densities (300 cycles at 50 mA cm−2, and 6000 cycles at 10 mA cm−2 under light illumination).